Prediction of parison formation using process data in extrusion blow molding - Tokunaga Tomohiro; Kajiwara Toshihisa; Nakayama Yasuya (Manufacturing Review)
In the extrusion process for plastic fuel tanks, laminated molten polymeric material is extruded and is molded into a hollow cylindrical shape called a parison. Accurately predicting the shape of a parison made from material of inhomogeneous viscoelasticity is a challenging issue. In this study, a numerical simulation based on process data is developed that is capable of predicting the parison shape during production. The process data (extrudate swell, drawdown, and temperature distribution) are collected from the production process and is utilized to develop a simulation model. Comparison of parison shapes extruded by production equipment against numerical simulations verifies for prediction of the distributions of the diameter and thickness of the parison shape to within ±20% of measured values, even under conditions different from those under which the data is obtained except for the data around large and fast stroke changes. The results show the possibility to predict parison shapes close to the one in production without directly solving the complex flow of inhomogeneous viscoelastic materials.